The impact of mindfulness on the wellbeing and performance of educators: A systematic review of the empirical literature. (January 2017) - Lomas, Tim; Medina, Juan Carlos; Ivtzan, Itai; Rupprecht, Silke; Eiroa-Orosa, Francisco José
Abstract: Given the potentially demanding nature of teaching, efforts are underway to develop practices that can improve the wellbeing of educators, including interventions based on mindfulness meditation. We performed a systematic review of empirical studies featuring analyses of mindfulness in teaching contexts. Databases were reviewed from the start of records to January 2016. Eligibility criteria included empirical analyses of mindfulness, mental health, wellbeing, and performance outcomes acquired in relation to practice. A total of 19 papers met the eligibility criteria and were included in the systematic review, consisting of a total 1981 participants. Studies were principally examined for outcomes such as burnout, anxiety, depression and stress, as well as more positive wellbeing measures (e.g., life satisfaction). The systematic review revealed that mindfulness was generally associated with positive outcomes in relation to most measures. However, the quality of the studies was inconsistent, and so further research is needed, particularly involving high-quality randomised control trials. Highlights: Offers a systematic review of the impact of mindfulness on the wellbeing of educational professionals. Provides a comprehensive assessment of the value of Mindfulness-Based Interventions. Covers a range of wellbeing outputs, including stress, anxiety, and depression. Offers recommendations for future research in this area.